SAT0537 Health-Related Quality of Life, Dependence and Need for Help after Total Knee Replacement. (23rd January 2014) - Nuñez, M.; Nuñez, E.; Sastre, S.; Lozano, L.; Sauló, A.; Nicodemo, C.; Segur, J. M.; Macule, F.
Abstract : Background: The need for help in daily activities is influenced not only by chronic diseases that present with disability and pain, such as knee osteoarthritis (OA), but also by psychosocial or economic factors, among others. Objectives: To assess health-related quality of life (HRQL), self-reported dependence and the need for help in patients with knee OA before and 12 months after total knee replacement. Methods: Prospective study with 12 months follow-up. HRQL was assessed using the validated Spanish version of the Short Form 36 (SF-36). Independence/dependence was assessed using the Barthel Index (BI), which measures help received during 10 daily activities (eating, washing, bathing, dressing, grooming, bladder continence, bowel continence, going to the toilet, moving from chair to bed, walking, climbing stairs), and the need for help by the number of hours per month of help required for activities of daily living (basic and/or instrumental: dressing, bathing, walking, household tasks, preparing meals, shopping, using transport, etc.)using a validated questionnaire. Sociodemographic and clinical variables were collected. Statistical analysis Differences between scores at baseline and 12 months were assessed using the Wilcoxon test for paired data. Results: 113 patients (84.1% female, mean age 69.40 years (SD 7.5), 77.5% retired or homemakers, were included. All patients had ≥1 comorbidities (mean 6.12 [SD 3.42]). The SF-36 showed that, at baseline, patients had significantly lower scores (<60% in physical function and < 15% in mental health) than the Spanish reference population. After 12 months follow up there were significant mean improvements in all dimensions, which reached > 20 points in the physical area (p <0.001), and reached values similar to the age- sex-matched reference population, except for pain, which was worse, and for women in the physical function dimension (worse). At baseline, 61.9% of patients were considered independent (score 100) according to the BI and the rest had mild dependence (score 85-95). Mean BI score was 96.02 (SD 6.6) and 96.06 (SD 6.96) at 12 months (p = 0.592). 72.6% of patients reported needing help to perform activities of daily living. The hours per month of help needed remained unchanged after surgery (mean 20.7 [SD 33.2] hours at baseline vs. 18. 3 [32.6] hours at 12 months, p = 0.370). Conclusions: Although HRQOLimproved significantly after surgery, it did not reach reference population values en the function and pain dimensions. Dependence, according to the Barthel Index, and the need for help did not change. This suggests thatdependence may not be related only to the underlying disease. This study was funded by the Spanish Ministry of Health grant FIS PS09/01148. Acknowledgements: This study was funded by the Spanish Ministry of Health grant FIS PS09/01148. Disclosure of Interest: None Declared